Development of Parliamentary Research Services in Central Europe and the Western Balkans - National Democratic Institute for international affairs (2014)
The following study offers a comprehensive summary of information and best practices in the development of parliamentary research services in parliaments of Central Europe, the Western Balkans1 and Slovenia, including an evaluation of the strength and weaknesses of different models and an assessment of existing challenges.